Association between dietary carbohydrate intake and multiple sclerosis risk: a large-scale cohort study - Yuan, Qi; Wang, Manli; Chen, Shuhui; Lin, Hao; Yang, Yudan; Zhao, Shuyue; Hua, Baojie; Guo, Jing; Sun, Xiaohui; Ye, Ding; Li, Jiayu; Mao, Yingying (Frontiers in Nutrition, 2025)
IntroductionMultiple sclerosis (MS) is a chronic autoimmune disorder characterized by neuroinflammation and demyelination. Although diet may influence MS risk, evidence regarding carbohydrate intake remains unclear.MethodsWe examined this association in a prospective cohort of 210,483 participants from the UK Biobank. Dietary carbohydrates were assessed using repeated 24-hour recalls. The diagnosis of MS cases was based on hospital inpatient records coded with the International Classification of Diseases, 10th Revision (ICD-10) code G35. The association between carbohydrate intake and MS risk was analyzed using Cox proportional hazards models.ResultsOver a median follow-up of 13.25 years, 495 incident MS cases were identified. A per interquartile range (IQR) increase in intake of total carbohydrates (HR = 1.21, 95% CI: 1.05–1.40), total sugars (HR = 1.23, 95% CI: 1.10–1.38), fiber (HR = 1.20, 95% CI: 1.08–1.33), fructose (HR = 1.25, 95% CI: 1.12–1.39), and glucose (HR = 1.20, 95% CI: 1.08–1.34) was associated with an increased risk of MS (all false discovery rate [FDR]-P < 0.05). Restricted cubic spline analyses showed linear dose–response relationships between these five carbohydrate types and MS risk (all Pnonlinear > 0.05). In addition, the associations between these carbohydrates and MS risk exhibited variations across different age and sex subgroups.DiscussionOur findings indicate that higher carbohydrate intake is associated with an increased risk of MS. Further studies are warranted to elucidate the underlying mechanisms.